THE CHARACTER EDUCATION IN ISLAMIC EDUCATION VIEWPOINT - Al Hamdani, Djaswidi (Jurnal Pendidikan Islam, 2016)
This paper intends to study the concept of character and moral education according to the terminology, approaches, and methods of learning from the point of view of Islamic education. The approach used in this paper is a discussion of the linguistic (al-lughah). The results showed that the conceptual basis of character education in the curriculum in Indonesia too much because it has a number of terminological problems. The concept of morals, values, and characters have a special meaning that may be different from one another. As a result, the concept of the character presented in the curriculum subject is far from the actual context of the moral and less with actually happening in the community. Character education is also too much use of the approach and methods indoctrinasi than critical, reflective and empirical and is not integrated with the system and school culture. Â 